Cell migration during heart regeneration in zebrafish. Issue 7 (10th May 2016) - Tahara, Naoyuki; Brush, Michael; Kawakami, Yasuhiko
Abstract : Zebrafish possess the remarkable ability to regenerate injured hearts as adults, which contrasts the very limited ability in mammals. Although very limited, mammalian hearts do in fact have measurable levels of cardiomyocyte regeneration. Therefore, elucidating mechanisms of zebrafish heart regeneration would provide information of naturally occurring regeneration to potentially apply to mammalian studies, in addition to addressing this biologically interesting phenomenon in itself. Studies over the past 13 years have identified processes and mechanisms of heart regeneration in zebrafish. After heart injury, pre‐existing cardiomyocytes dedifferentiate, enter the cell cycle, and repair the injured myocardium. This process requires interaction with epicardial cells, endocardial cells, and vascular endothelial cells. Epicardial cells envelope the heart, while endocardial cells make up the inner lining of the heart. They provide paracrine signals to cardiomyocytes to regenerate the injured myocardium, which is vascularized during heart regeneration. In addition, accumulating results suggest that local migration of these major cardiac cell types have roles in heart regeneration. In this review, we summarize the characteristics of various heart injury methods used in the research community and regeneration of the major cardiac cell types. Then, we discuss local migration of these cardiac cell types and immune cells during heart regeneration. Developmental Dynamics 245:774–787, 2016 . © 2016 Wiley Periodicals, Inc. Key findings: We describe injury methods and characteristics of major cardiac cell types during heart regeneration in zebrafish. We discuss local cell migration in the heart during heart regeneration in zebrafish.